2017
DOI: 10.1111/ajag.12411
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden, comorbidity and geriatric syndromes in the Australian aged care population

Abstract: The challenges for evaluating clinical care in Australian residential aged care are many. Delivering good clinical care should be a priority for aged care providers given the high burden of chronic disease and comorbidity. An informative starting point could be to target management of the most prevalent and burdensome conditions and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 9 publications
0
41
2
1
Order By: Relevance
“…before the ACFI). ACAP allows up to ten conditions to be reported, and studies that used ACAP(16) data have found generally higher prevalence rates for conditions than those based on ACFI data, but both sources report generally lower rates than our estimates from EHR data (17). As for survey data, our prevalence estimates for most conditions also tended to be higher; compared to estimates from the Australian Bureau of Statistics Survey of Disability, Ageing and Carers in 2015 for respondents in residential aged care, our prevalence estimates are similar for arthritis, but higher for osteoporosis, anxiety, depression, hypertension and diabetes (20).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…before the ACFI). ACAP allows up to ten conditions to be reported, and studies that used ACAP(16) data have found generally higher prevalence rates for conditions than those based on ACFI data, but both sources report generally lower rates than our estimates from EHR data (17). As for survey data, our prevalence estimates for most conditions also tended to be higher; compared to estimates from the Australian Bureau of Statistics Survey of Disability, Ageing and Carers in 2015 for respondents in residential aged care, our prevalence estimates are similar for arthritis, but higher for osteoporosis, anxiety, depression, hypertension and diabetes (20).…”
Section: Discussioncontrasting
confidence: 63%
“…These differences were more pronounced for some conditions. For example, we found higher prevalence rates based on residents' EHR data for the three most common conditions compared to those identified with ACFI data alone: dementia (58% vs. 48%), depression (54% vs. 23%) and arthritis (61% vs. 14%) (17). Our results suggest that ACFI data alone may generally underestimate condition prevalence, but the magnitude of underestimation varies by condition.…”
Section: Discussionmentioning
confidence: 49%
“…Most people entering RACS require 24‐hour care and support: 60% need assistance with feeding, dressing, personal hygiene and mobility; 72.1% have high needs related to dementia behaviours; and 61.3% have complex health‐care needs including chronic illnesses such as dementia. These illnesses severely impact on individual care needs and functional ability . The projected doubling of Australians aged ≥85 years plus over the next two decades will drive the demand for residential aged care .…”
Section: Introductionmentioning
confidence: 99%
“…These illnesses severely impact on individual care needs and functional ability. 4 The projected doubling of Australians aged ≥85 years plus over the next two decades will drive the demand for residential aged care. 5 Ideally, the provision of evidence-based aged care should be built on rigorous research involving both residents and staff.…”
mentioning
confidence: 99%
“…More than half of the papers in this virtual issue highlight the care and system needs for people with dementia. For example, Hillen et al highlight that there are 170 000 Australians living in aged care facilities, but limited understanding of the disease burden in this group. They review ACFI data for 169 000 residents, finding a high level of complex morbidities, with dementia, depression and circulatory disease, the most prevalent conditions in patterns of comorbidity.…”
mentioning
confidence: 99%